2003
DOI: 10.1002/sce.10112
|View full text |Cite
|
Sign up to set email alerts
|

Remote atomic force microscopy of microscopic organisms: Technological innovations for hands‐on science with middle and high school students

Abstract: ABSTRACT:This study examined hands-on experiences in the context of an investigation of viruses and explored how and why hands-on experiences may be effective. We sought to understand whether or not touching and manipulating materials and objects could lead to a deeper, more effective type of knowing than that we obtain from sight or sound alone. Four classes of high school biology students and four classes of seventh graders participated in the study that examined students' use of remote microscopy with a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…1), which employs a haptic force-feedback device that translates SPM signals into kinesthetic sensory experiences [Taylor et al, 1993]. This tool has been introduced into educational settings by Jones and colleagues, who have employed a web-based interactive interface to allow school learners to remotely operate an AFM [Jones et al, 2004]. The same research group has also used pre-recorded AFM data to allow the integration of multiple options for exploration of data without requiring access to the actual laboratory equipment .…”
Section: A Microscope Probe-based Multisensory Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…1), which employs a haptic force-feedback device that translates SPM signals into kinesthetic sensory experiences [Taylor et al, 1993]. This tool has been introduced into educational settings by Jones and colleagues, who have employed a web-based interactive interface to allow school learners to remotely operate an AFM [Jones et al, 2004]. The same research group has also used pre-recorded AFM data to allow the integration of multiple options for exploration of data without requiring access to the actual laboratory equipment .…”
Section: A Microscope Probe-based Multisensory Platformsmentioning
confidence: 99%
“…Although the set of reviewed publications represent our own opinion of the principle contributions in this area, it may not necessarily be an exhaustive account of all published work available on the topic. Jones et al (2003Jones et al ( , 2004 Nanometer scale; microscale; virus morphology and dimensionality (2003,2004); virus characteristics such as shape, composition, and size; properties and behavior of nanoscale objects (2006) Probe microscopy in combination with a visuohaptic virtual platform…”
Section: Research On the Influence Of Interactive Visualization Imentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some researchers have explored the effect of haptic augmentation of instruction on size and scale understandings [23,24]. For example, Jones et al [23] found that students in both limited-haptic and full-haptic environments made significant gains in their understandings of nanometer scale.…”
Section: Additional Influences On Conceptions Of Size and Scalementioning
confidence: 99%
“…For example, Jones et al [23] found that students in both limited-haptic and full-haptic environments made significant gains in their understandings of nanometer scale. Specifically, students in both treatment groups were more likely to identify examples of nano-sized objects and describe the degree to which a human would have to be shrunk to reach the size of a virus.…”
Section: Additional Influences On Conceptions Of Size and Scalementioning
confidence: 99%